Plasma Spheroidisation of Irregular Ti6Al4V Powder for Powder Bed Fusion - Nthateng Nkhasi (MDPI AG, 2021)
Metal powders suitable for use in powder bed additive manufacturing processes should ideally be spherical, dense, chemically pure and of a specified particle size distribution. Ti6Al4V is commonly used in the aerospace, medical and automotive industries due to its high strength-to-weight ratio and excellent corrosion resistance properties. Interstitial impurities in titanium alloys have an impact upon mechanical properties, particularly oxygen, nitrogen, hydrogen and carbon. The plasma spheroidisation process can be used to spheroidise metal powder consisting of irregularly shaped particles. In this study, the plasma spheroidisation of metal powder was performed on Ti6Al4V powder consisting of irregularly shaped particles. The properties of the powder relevant for powder bed fusion that were determined included the particle size distribution, morphology, particle porosity and chemical composition. Conclusions were drawn regarding the viability of using this process to produce powder suitable for additive manufacturing.